Achievements of Pencak Silat Athletes: The Role of Parents and Coaches - Alang, Ashari; Jalil, Rasyidah; Kahar, Irsan; Ahmad, Ahmad (Department of Physical Education, Sport, Health and Recreation, 2023)
Pencak silat, one of the martial arts sports, is one of Indonesia's ancestral heritage which is widely spread throughout the archipelago. In the current development of pencak silat, it tends to become an achievement sports with high competition, thus encouraging athletes to improve their abilities. For sports, achievement is more directed at competition which ends with